2019
DOI: 10.2174/0929867324666170720160632
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Diet and Reduction of Chronic Disease Risks of Night Shift Workers

Abstract: A healthy diet and improved dietary practices, together with other factors, can reduce shift workers' chronic disease risk. The literature showed the importance of eating behaviour in order to prevent diseases in these workers; therefore, educational programmes are necessary to encourage several important lifestyle changes. The target of our future research will be the role of food components in some dietetic habits for the prevention of disease in night shift workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 141 publications
1
6
0
Order By: Relevance
“… 14 18 37 With respect to quality of diet, a few studies observed alterations in eating habit and specific nutrient intake among shift workers relative to day workers. 17 18 19 However, owing to limitations in study design and variability in defining shift work and assessing dietary intake, results are difficult to compare between studies. In our previous study in the NHS II, history of night shift work was not associated with quality of diet, 14 but no study has investigated the overall diet quality across different shift work categories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 14 18 37 With respect to quality of diet, a few studies observed alterations in eating habit and specific nutrient intake among shift workers relative to day workers. 17 18 19 However, owing to limitations in study design and variability in defining shift work and assessing dietary intake, results are difficult to compare between studies. In our previous study in the NHS II, history of night shift work was not associated with quality of diet, 14 but no study has investigated the overall diet quality across different shift work categories.…”
Section: Discussionmentioning
confidence: 99%
“… 9 10 11 12 Among shift workers, excess adiposity and increased smoking are frequently and consistently reported, 13 14 15 whereas the evidence on physical activity is mixed. 16 Some studies observed alterations in eating habit and specific nutrient intake among shift workers, 17 18 19 but the evidence on overall quality of diet across different shift work categories is sparse. To our knowledge, no previous study has examined the joint associations of duration of rotating night shift work and unhealthy lifestyle factors with risk of type 2 diabetes or evaluated their potential interactions.…”
Section: Introductionmentioning
confidence: 99%
“…
The possible effects of hunger-satiety cycle perturbation in shift workers is related to the interaction of two factors49,50,51 ) :• changes in meal times• the hunger experienced during night shifts, which leads to food intake.Qualitative and quantitative information on the eating habits of shift workers can be collected by direct interviews or through a food diary52 ) . Deviations from healthy eating can be corrected by formulating diets appropriate to the shift work or by asking companies to provide healthier food in canteens and vending machines53,54,55 ) .Unhealthy eating habits can promote overweight, obesity, and cardiovascular diseases (CVDs) like type 2 diabetes (T2D), dyslipidemia, metabolic syndrome (MS) and myocardial infarction, and further affect the poor sleep patterns of shift workers56, 57 ) .
…”
Section: Outputs Of the Biological Clockmentioning
confidence: 99%
“…Unhealthy eating habits can promote overweight, obesity, and cardiovascular diseases (CVDs) like type 2 diabetes (T2D), dyslipidemia, metabolic syndrome (MS) and myocardial infarction, and further affect the poor sleep patterns of shift workers56, 57 ) .…”
Section: Outputs Of the Biological Clockmentioning
confidence: 99%
“…Unhealthy food creates problems and causes many diseases all over the world, fast food is a global issue and its rate of consumption increases day by day. Eating a poor‐quality diet of junk food is highly linked to a risk of obesity and digestive issues (Ferri, Cavone, Intranuovo, & Macinagrossa, ). Many fast‐food meals have an extra amount of sugar that affect the human respiratory system (Fuhrman, ).…”
Section: Introductionmentioning
confidence: 99%